Educational and Cultural Diffusion in of States Brazilian Public Archives - Santos, Keyla (2014)
Public archives are ceasing to be essentially repositories of administrative documents to also achieve their social role. Can promote cultural and educational nature activities. Therefore, this study aims to identify and analyze the cultural and educational activities that are developed by the Brazilian state archival institutions, and conduct a comparative study between the institutions about the actions promoted by exposing their realities and potentialities. The research is characterized as qualitative in nature, encompassing a research survey and documentary. On the instruments for data collection, questionnaires to managers of institutions was utilized, and script analysis of institutional electronic sites. The results show that the main cultural and educational activities performed by files are exhibitions, visits and publications, highlighting the files of the states of São Paulo and Rio Grande do Sul for diversity and systematics in the production of such actions.